A complicated simple fall – an atypical case of serogroup Y meningococcal pneumonia with secondary septicaemia and literature review. (4th April 2012) - Chan, BKY; Kudsk-Iversen, S; Balaguruswamy, S; Purewal, TS
Abstract : An elderly lady was admitted for pain management and rehabilitation following a fall. During her stay she developed a new heart murmur and sepsis. Subacute bacterial endocarditits was excluded, empirical ciprofloxacin was initiated and later converted to aztreonam with gentamicin for clinical deterioration. Subsequent investigations revealed meningococcal Y septicaemia secondary to pneumonia, with a possible oropharynx focus. Upon discharge she had returned to baseline state. The case reflects an unusual and increasing cause of pneumonia. A steady increase of infective serogroup Y isolates over the past 12-years in England, with tendency towards elderly makes it a significant differential among the general medical population. This trend corresponds with the US, but is yet unknown whether to be a periodic cycle or true change in dominance and, or, virulence among serogroups. If the latter were true, it would support the inclusion of serogroups beyond menigitides C in the vaccination program.